Síntese de membranas de alumina anódica porosa sobre substratos metálicos obtidos por evaporação térmica - Garcia, Uanderson Mezavila (2017)
This work covers the investigation and synthesis of nanometric structures of Porous Anodic Alumina PAA, produced from low purity substrates, in aim to obtain selfsustained membranes. The Hard Anodization (HA) and Mild Anodization (MA) processes were used under special conditions through those found in literature. The analyses of results were based in comparing the AAP produced under the same conditions except the applied potential that was different depending on the MA or HA. HA process had its time halved in order to investigate the oxide growth rate and to calibrate the conditions of anodized membrane synthesis over the glass samples. This work also covers the construction of a resistive thermal evaporation PVD system capable of evaporating metals with melting points below 800°C. Through the deposition of successive layers it was possible to obtain metallic films of aluminum with thicknesses above 10 µm, enabling conditions of synthesis of porous anodic alumina on substrates produced by thermal resistive evaporation. The result of membrane synthesis on low purity aluminum substrates was complement to the synthesis of membranes obtained in aluminum evaporated in glass substrates, since the thickness of each deposited film is low if compared to the thickness of the AAP layer. Therefore, it was necessary to make several Al depositions on the same samples, to obtain an aluminum film that was able to support an oxide layer of anodic alumina and with the same characteristics of those obtained by the process of MA. All anodized samples were characterized by scanning electron microscopy, including samples made from metalized aluminum. The micrography obtained from the low purity aluminum membranes were treated by ImageJ software allowing the morphological analysis. AAP membranes obtained from technical Al substrate depicted the formation of branched pore channels, a result of instabilities in applied electric field during Anodization and presence of different alloying elements in the Al substrate. The metalized aluminum film had a larger thickness in the samples positioned in the middle of the sample holder possibly due to different temperature gradients of filament depending on the position of Al pellets.